ECOBRICK: ELEMEN DESAIN ESTETIS DAN EKOLOGIS DI DESA WISATA NGERANGAN, KLATEN - Ristianti, Novia Sari; Widjajanti, Retno; Kurniati, Rina; Nurini, Nurini (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2021)
Abstract: Waste management as a cost recovery has an economical selling value. Such as the Ecobrick concept. Ecobrick utilizes non-biological waste, converted into small pieces (bricks) and then put into plastic bottles. Plastic waste will be stored and preserved in the bottle. The household furniture is made from ecobricks such as tables, chairs, and walls. Therefore, Ecobrick can improve aesthetic and ecological functions in Kampoeng Loempang Ngerangan Tourism Village.The aim is to implement 3R waste processing through ecobricks in improving aesthetic and ecological functions in Kampoeng Loempang Ngerangan, Klaten Regency.The research method is quantitative. Stage I information is about techniques, principles, and products of Ecobricks. Stage II Guidance is implemented making ecobrick and its product. Stage III Practice is making and arranging ecobricks into buildings and furniture. Phase IV Independence and Habitual is the evaluation of Ecobrick products used for the aesthetic and ecological functions of Kampoeng Loempang. Such as a gate, stalls, tables, and chairs.The research output is implementing ecobrick technology in Kampoeng Loempang Ngerangan Tourism Village in aesthetic and ecological element designs for entrance gates as landmarks, stalls culinary tourism, and chairs and dining tables for culinary tours.Keywords: ecobrick, aesthetic, ecology, rural tourismÂ Abstrak: Pengelolaan sampah sebagai cost recovery memiliki nilai jual yang ekonomis. Seperti konsep Ecobrick yang memanfaatkan sampah non hayati, diubah menjadi potongan-potongan kecil (bata) kemudian dimasukkan ke dalam botol plastik. Sampah plastik akan disimpan dan diawetkan dalam botol. Perabotan rumah tangga terbuat dari ecobrick seperti meja, kursi, dan dinding. Oleh karena itu, Ecobrick dapat meningkatkan fungsi estetika dan ekologi di Desa Wisata Kampoeng Loempang Ngerangan. Tujuan kegiatan ini yaitu untuk menerapkan pengolahan sampah 3R melalui ecobrick dalam meningkatkan fungsi estetika dan ekologi di Kampoeng Loempang Ngerangan, Kabupaten Klaten. Metode penelitian adalah kuantitatif. Informasi tahap I adalah tentang teknik, prinsip, dan produk Ecobrick. Tahap II Bimbingan dilaksanakan pembuatan ecobrick dan produknya. Tahap III Praktek membuat dan menata ecobrick menjadi bangunan dan furniture. Tahap IV Kemandirian dan Pembiasaan adalah evaluasi produk Ecobrick yang digunakan untuk fungsi estetika dan ekologi Kampoeng Loempang. Seperti gapura, warung, meja, dan kursi. Luaran kegiatan ini adalah mengimplementasikan teknologi ecobrick di Desa Wisata Kampoeng Loempang Ngerangan dalam desain elemen estetika dan ekologi untuk gerbang masuk sebagai landmark, warung wisata kuliner, dan kursi dan meja makan untuk wisata kuliner.Kata Kunci: ecobrick, estetika, ekologis, desa wisata